MINI 11 a Microcontroller Laboratory Hardware Platform with IDE Approach - Nik Mohd Kamil, Nik Yusof; Selvakumar, Raja Saravana Kumar; Kamarul Hawari, Ghazali (2010)
Microcontroller technology has become a core subject in many electrical and electronic fields. Ironically, students envisage difficulty of understanding the material in this course. Hand-on laboratory or project-based design is the key element to student knowledge retention and ability to apply the knowledge in practical endeavors. However, it is difficult to find a portable and low cost prototype system that can meet the individual demand in the market. This paper aims to describe development of a flexible microcontroller training system based on 8-bit Motorola family (MINI11) with a simple testing-bed. In addition, it is further boosted by the introduction of Integrated Development Environment (IDE) features in order to create user-friendly environment thus offering a simple approach to learn this embedded device in short time Keywords: IDE, microcontroller